Anniversary article Interactional feedback in second language teaching and learning: A synthesis and analysis of current research. (July 2016) - Nassaji, Hossein
The role of interactional feedback has long been of interest to both second language acquisition researchers and teachers and has continued to be the object of intensive empirical and theoretical inquiry. In this article, I provide a synthesis and analysis of recent research and developments in this area and their contributions to second language acquisition (SLA). I begin by discussing the theoretical underpinnings of interactional feedback and then review studies that have investigated the provision and effectiveness of feedback for language learning in various settings. I also examine research in a number of other key areas that have been the focus of current research including feedback timing, feedback training, learner–learner interaction, and computer-assisted feedback. The article concludes with a discussion of the implications of the issues examined with regard to classroom instruction.